I am a story - Yaccarino, Dan (Harper, an imprint of HarperCollinsPublishers, 2016)
Author-illustrator Dan Yaccarino presents a powerful picture book that celebrates storytelling from the past to the present and beyond. From cave drawings to the invention of the printing press to our digital age, discover how a story has been told in many different ways from the past to today. It's always been around, making us happy, sad, excited, or scared and bringing people together. With simple text and delightful illustrations, Dan Yaccarino reminds us of the power of story.